2003
DOI: 10.1002/dei.137
|View full text |Cite
|
Sign up to set email alerts
|

Literacy and the role of parents of deaf children

Abstract: This study focuses on the involvement of parents in the reading development of their deaf children and gathers evidence on parental experiences of reading with their child at home. Of particular interest is the relationship between teachers and parents working as partners in establishing a literacy environment for deaf children. It is concluded that uncertainty in professional practice about methods of developing literacy in deaf children could be one of the reasons why confident support is not always offered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Shared picture book reading, for example, is interactional and an important activity for the acquisition of both spoken and written language (Heineman-Gosschalk & Webster, 2003). This form of reading is structured and predictable for the child and forms a framework in which learning about text takes place-specifically, the provision of labels for the pictures-that adds to the child's vocabulary.…”
Section: Language Experiencementioning
confidence: 99%
“…Shared picture book reading, for example, is interactional and an important activity for the acquisition of both spoken and written language (Heineman-Gosschalk & Webster, 2003). This form of reading is structured and predictable for the child and forms a framework in which learning about text takes place-specifically, the provision of labels for the pictures-that adds to the child's vocabulary.…”
Section: Language Experiencementioning
confidence: 99%
“…Gioia (2001), however, found that although literacy practices were established in the homes, shared reading rituals between parents and their deaf children were not always established. Although parents enjoyed reading with their children who are deaf they experience obstacles in the reading process (Heinemann-Gosschalk & Webster, 2003). Mirenda and Erickson (2000) also explored the use of AAC in facilitating literacy in children with autism.…”
Section: Emergent Literacy: the Importance Of Home-based Literacy Expmentioning
confidence: 99%